Impact of Microfinance Institutions on Economic Growth of Nepal - Oli, Sudan K. (Asian Journal of Economic Modelling, 2018)
This study examines the impact of microfinance institutions on economic growth of Nepal. Gross domestic product and per capita income are the dependent variables. The independent variables are total number of staffs, total number of members, microenterprises credit, total assets, total loan, total deposit, inflation and broad money supply. The study is based on secondary sources of data. The data have been collected for the period of 2012/13 to 2016/17 from 24 microfinance institutions leading to a total of 120 observations. The data are collected from Bank Supervision Report, Quarterly Economic Bulletin published by Nepal Rastra Bank and Economic Survey 2016/17 published by Ministry of Finance. The multiple regression models are estimated to test the significance and impact of microfinance institutions on economic growth of Nepal. The study shows that the total number of staffs, total number of members, ratio of microenterprises loan, total assets, total loan, total deposit and broad money supply growth are positively related to economic growth. It indicates that larger the number of staffs and members of micro-finance institutions, higher would be the economic growth. The results also show that increase in total assets and total loan leads to increase in economic growth. Likewise, the study reveals that higher the amount of total deposits, higher would be the economic growth. Similarly, the study shows that higher the money supply, higher would be the economic growth. However, result shows that there is a negative relationship between inflation and economic growth in Nepal. This indicates that higher the inflation, lower would be the economic growth.